Adsorption of sulfathiazole drug on the platinum-decorated zinc oxide nanotubes. (1st November 2020) - Su, Xiaojie; Yang, Shehua; Song, Yuxia; Li, Jing; Wei, Lixiao; Zhao, Jing
Abstract : Experimental studies have shown that the decoration of a metal oxide nanostructure by the noble metals increases its sensitivity toward different chemicals to a great extent. Here, the sensing properties of a pristine ZnO nanotube (ZnON) and its Pt-decorated form (Pt@ZnON) were investigated toward the sulfathiazole (STZ) drug by implementing density functional theory calculations. The pristine ZnON adsorbs the STZ drug weakly with the adsorption energy (Ead ) of –5.2 kcal/mol, and cannot detect it because of a minor sensing response of 3.38 at room temperature. A Pt atom was decorated on the ZnON surface with the Ead of –45.2 kcal/mol. Pt-decoration increased the Ead of STZ and the sensing response of the ZnON to −35.5 kcal/mol and 485.27, respectively. We concluded that the Pt@ZnON could be a promising candidate for application in the STZ drug sensors. A short recovery time of 12 s was also predicted for Pt@ZnO-based sensor. GRAPHICAL ABSTRACT: